2013
DOI: 10.1016/j.jtcvs.2013.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the aged heart during cardiac surgery: Use of del Nido cardioplegia provides superior functional recovery in isolated hearts

Abstract: Del Nido cardioplegia prevents spontaneous contractions during arrest, reduces troponin release, and results in superior myocardial function in isolated aged hearts. Del Nido cardioplegia has the potential to provide superior myocardial protection for older patients undergoing cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 34 publications
3
79
0
3
Order By: Relevance
“…The potential benefits of DNC have also been corroborated in experimental studies. Several animal models comparing DNC to other cardioplegic solutions have demonstrated superiority in reduction of electrical activity after arrest and decrease calcium accumulation in myocytes …”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits of DNC have also been corroborated in experimental studies. Several animal models comparing DNC to other cardioplegic solutions have demonstrated superiority in reduction of electrical activity after arrest and decrease calcium accumulation in myocytes …”
Section: Discussionmentioning
confidence: 99%
“…Later, they also showed that, in a similar setting of aged hearts, single-dose DN cardioplegia was also associated with superior calcium handling of cardiomyocytes, reduced myocardial injury, and improved functional recovery [13]. However, these findings need to be confirmed using more clinically relevant methodology, and their effect on long-term post-operative ventricular function should be examined.…”
Section: Discussionmentioning
confidence: 99%
“…4 Given the ease of administration, and the potential for reducing surgical interruption and cost, interest in del Nido solution has been increasing in the adult cardiac community. 4 Although there is a large body of unpublished experience regarding its use in adults at some centers, and a small amount of animal data, 5,6 published clinical data are scant. No randomized trial has been launched to investigate the comparative safety of these 2 cardioplegia methods.…”
mentioning
confidence: 99%